Sistem Informasi Penghitungan Kebutuhan Gizi Ibu Hamil Menggunakan Metode Harris Benedict - Nida Fitrillah; Wasis Haryono (CV. Multi Kreasi Media, 2022)
The Red Delima Posyandu, which is located in Mulyasari village, Cirebon, regularly carries out health activities, including opening consultations for pregnant women, in order to meet nutritional needs during pregnancy. However, the method applied at the time of calculation still uses an inaccurate method. The calculation and consultation data input is still manual using a notebook which often results in damage to the data, such as unclear writing or even missing data. Information obtained by pregnant women from posyandu is still not effective. So that in the process of data collection and delivery of information becomes inefficient. To overcome this problem, an information system is needed that can calculate nutrition using the Harris Benedict method that can be accessed by posyandu cadres, accompanied by consultation data management by midwives and information forums for pregnant women. Development of a web-based information system using the waterfall method with the aim of providing convenience in managing data for pregnant women, with the right method by Harris Benedict. Ease of management of consultations by midwives and ease of accessing information regarding nutritional needs for pregnant women. Keywords: Information Systems, Pregnant Women, Nutrition, Harris Benedict, Posyandu